Amino Acid‐Based Low‐Dimensional Management for Enhanced Perovskite Solar Cells. Issue 7 (29th April 2022) - Hu, Yingjie; Gao, Lili; Su, Hang; Du, Xinyi; Yuan, Ningyi; Ding, Jianning; Zhang, Jing; Liu, Shengzhong (Frank)
Abstract : It has been reported that an overlayer of lower dimensional perovskite can effectively improve the properties of 3D perovskite solar cells. Here, 4‐aminobutyric acid (C4I) and 6‐aminocaproic acid iodides (C6I) are introduced onto the surface of the perovskite layer, forming a low‐dimensional (LD) capping layer on the 3D perovskite films for high‐performance devices. It is found that C4I forms a 2D perovskite layer, while C6I forms a 1D perovskite layer on the 3D perovskite surface. By using the LD capping layers, the integrated perovskite films show passivated surface traps, reduced defect density, improved carrier lifetimes, and altered band alignment, leading to improved fill factor and open‐circuit voltage and, hence, significantly higher device efficiency. The devices with the C4I and C6I capping layers achieve solar cell efficiencies as high as 23.48% and 23.11%, respectively. In addition, bare devices with the C4I and C6I integration maintain 93.73% and 91.58%, respectively, of their initial efficiencies after exposure to the ambient atmosphere for 2000 h, demonstrating much better stability than the pristine 3D holding only 83.30% of its initial efficiency. It appears that this 2D capping is more suitable for enhancing 3D perovskite performance for general photoelectronic applications than the 1D capping. Abstract : The devices with 4‐aminobutyric acid and 6‐aminocaproic acid iodides forming 2D and 1D capping layers on the 3D films achieve high efficiencies of 23.48% and 23.11%, respectively, and show stable stability maintaining 93.73% and 91.58% of their initial efficiencies, respectively, after 2000 h exposure in atmosphere. 2D capping is more suitable for enhancing 3D perovskite performance than the 1D capping.